Anti-Müllerian hormone and progesterone levels in human follicular fluid are predictors of embryonic development - Yvonne O'Brien; Mary Wingfield; Lynne C. O'Shea (BMC, 2019)
Abstract Background Human follicular fluid is an intricate biological fluid contributing to the developing oocyte microenvironment. Accumulating evidence suggests that sex hormones present in follicular fluid (FF) may play an important role in regulating oocyte developmental potential. The aim of this study was to determine if anti-Müllerian hormone (AMH) and progesterone (P4) levels in FF are correlated with oocyte quality as defined by subsequent embryonic development. Methods This was a prospective cohort study of 88 women undergoing IVF/ICSI at a university associated fertility clinic. Follicular fluid was collected from the first follicle aspirated at the time of oocyte retrieval. The corresponding oocyte was individually cultured in order to track its developmental outcome. FF-AMH and P4 concentrations from follicles where the oocyte fertilised normally and developed into a blastocyst on day 5 (Group 1: BLAST, n = 23) were compared with FF from follicles where the oocyte fertilised normally but failed to reach blastocyst stage by day 5 (Group 2: FERT, n = 19). No significant differences were observed between the two groups in terms of maternal age, body mass index, previous live births, previous pregnancy loss, number of antral follicles, number of oocytes recovered, IVF:ICSI ratio or percentage of recovered oocytes that fertilised. Results FF-AMH and P4 levels were significantly increased in Group 1: BLAST compared to Group 2: FERT (P = 0.007 and P = 0.013 respectively). Twenty-one FF samples had an AMH level > 15 pmol/L, of which 17 related to oocytes that progressed to blastocyst stage, providing a positive prediction value (PPV) of 76.96%. Eleven FF samples had a P4 level > 60 mg/ml, of which 10 progressed to blastocyst stage, providing a PPV of 90.99%. Six samples had an AMH level > 15 pmol/L and a P4 level > 60 mg/ml, of which 100% progressed to blastocyst stage, providing a PPV of 96.83%. Conclusions FF-AMH and P4 levels from individual follicles can accurately predetermine subsequent embryonic development. Combining follicular fluid analysis with routine morphological assessment, could allow for a more accurate and sensitive method of determining embryonic developmental competence.